9(3x+7)+33=-3(11x+8)

Simple and best practice solution for 9(3x+7)+33=-3(11x+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(3x+7)+33=-3(11x+8) equation:


Simplifying
9(3x + 7) + 33 = -3(11x + 8)

Reorder the terms:
9(7 + 3x) + 33 = -3(11x + 8)
(7 * 9 + 3x * 9) + 33 = -3(11x + 8)
(63 + 27x) + 33 = -3(11x + 8)

Reorder the terms:
63 + 33 + 27x = -3(11x + 8)

Combine like terms: 63 + 33 = 96
96 + 27x = -3(11x + 8)

Reorder the terms:
96 + 27x = -3(8 + 11x)
96 + 27x = (8 * -3 + 11x * -3)
96 + 27x = (-24 + -33x)

Solving
96 + 27x = -24 + -33x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '33x' to each side of the equation.
96 + 27x + 33x = -24 + -33x + 33x

Combine like terms: 27x + 33x = 60x
96 + 60x = -24 + -33x + 33x

Combine like terms: -33x + 33x = 0
96 + 60x = -24 + 0
96 + 60x = -24

Add '-96' to each side of the equation.
96 + -96 + 60x = -24 + -96

Combine like terms: 96 + -96 = 0
0 + 60x = -24 + -96
60x = -24 + -96

Combine like terms: -24 + -96 = -120
60x = -120

Divide each side by '60'.
x = -2

Simplifying
x = -2

See similar equations:

| 15+3(x+2)=7(x-1)x(2x-7) | | 2.5x+2.0=0.7+5.6 | | 3x^2-6x-87= | | 63x+27x^2= | | x+14=180-(2x+16) | | 3(2x+1)=11(8-x)2(7x-4) | | -4(x+6)+2(x-2)=0 | | 5x-(4x+9)=5x-21 | | 4.3x=63.43 | | 2[x-1(4+2x)+3]=2x+2 | | 8+2(x-3)=4(x-5)3(20-x) | | -5(3-r)+4=5r-11 | | 1/2b-2=1/4 | | 3-7x-1=5 | | x^2+2.6x+1.68=0 | | 6(10-x)=3(3x-5)9(2x-1) | | 18-7(3-x)=0 | | 3y+7=4x-7+9 | | 5(y-3)+2=4(2y+5) | | 13x+1=5(3+2x)+x | | -6(y+2)-3=15 | | z+18=32 | | 24-[5+6y-3(y+3)]=-4(5y-7)-[6(y-1)-16y+20] | | 9x+16=52 | | 2+3(12-x)=2(x-6)8(x+1)+1 | | 12(s+.66)=10.4 | | 5(x+y)-x+y=-4 | | 3(9-5t)-5(9-10t)=7 | | y-19=-2 | | 5(9+2x)=32-x | | q(x+2)=-x^2+4x+1 | | 2(b+83.33)=416.66 |

Equations solver categories